What might David do in the face of Goliath? The effects of height on status-signaling behaviours in males - CHEN, Nicole Ruiying (Institutional Knowledge at Singapore Management University, 2023)
While the extant literature has looked mainly at how attractive, opposite-sex stimuli impacts our behaviour, much less is known regarding how exposure to same-sex stimuli may also wield influence on human behaviors. Proffering an evolutionary-based perspective, this study aims to investigate, in a sample of heterosexual males, how exposure to taller same-sex stimuli will differentially influence conspicuous status-signaling behaviors of shorter males compared to taller males, in the context of a mating motive. Two competing hypotheses are proposed: (1) shorter males will display greater conspicuous status-signaling compared to taller males in the presence of a tall male confederate and (2) taller males will display greater conspicuous status-signaling compared to shorter males in the presence of a tall male confederate. To test the prediction, a quasi-experimental mixed design was used, and heterosexual male participants were recruited from Singapore Management University as well as the general public (N =60). Participants were randomly assigned to either a shorter or taller male confederate condition, with an attractive female confederate present in both conditions. Spending on status items and their willingness to spend in the form of a reservation price were assessed as dependent variables. Results offered little support to either hypotheses, although there is some consistent evidence pointing towards taller males spending more than shorter males in the presence of a taller male confederate. Alternative explanations, limitations and future recommendations are discussed.